(untitled) (Journal of Hama University, 2022)
A field experiment was conducted to evaluate the influence of adding treated organic residues (treated olive mill wastewater (OMW) and biochar (B)) on growth, flowering and corm production of Freesia hybrida grown in calcareous soil, in Lattakia, during the seasons 2018-2019 and 2019-2020. The experiment included 5 treatments: (T1: Control without any additions, T2: mineral fertilization of NPK (30:20:20) g2+ 2 Kg m2 of organic manure, T3: 7 l m2 of OMW, T4: 2 Kg m2 of B and T5: 3,5 l m2 of OMW + 2 Kg m2 of B). Treatment T5 has close results to farmer treatment T2, with no significant differences between these two for some of studied vegetative parameters (plant height, leaf number and leaf content of phosphorus). No significant differences were recorded somewhere in the range of T3 and T5 for most vegetative parameters, additionally best results for both leaf content of chlorophyll and % of dry matter were recorded in T3. Results have showed that all fertilization treatments were superior to control, and for all studied vegetative and flowering parameters. No significant differences were recorded somewhere in the range of T2 and T3 for (number of flowers per spike, length of flower stalk and spike fresh weight). That T1 and T5 have accomplished early flowering, while the longest flowering duration was recorded in both T2 and T5. Treatment T5 has accomplished the highest percentage of cormels < 1 cm in diameter (47,43%), and was significant superior to all other studied treatments.